Synthesis of benzylidenecycloalkan-1-ones and 1,5-diketones under Claisen–Schmidt reaction: Influence of the temperature and electronic nature of arylaldehydes - Lantaño, Beatriz (2017)
Herein, we present the results of the influence of reaction temperature and the electronic nature of arylaldehydes in the reactions of benzocycloalkan-1-ones and arylaldehydes under classical Claisen–Schmidt condensation conditions. The products obtained, 2-arylidene derivatives of benzocycloalkan-1-ones and/or spiropolycyclic-1,5-diketones through multicomponent reactions, depended on the electronic nature of arylaldehyde and the reaction temperature. Besides, under identical conditions, 2-arylideneindan-1-ones afforded bis-indane-1,5-diketones through a process that involves Michael addition reaction, which is also dependent on the temperature. Theoretical studies using density-functional theory allowed understanding the chemical reactivity and the site selectivity of α,β-enones used in this work through the calculation of global and local electrophilicity on C–β. Both the electrophilicity of C-β and the temperature led the course of reaction toward the formation of aldol condensation, aldol condensation/Michael addition, and aldol condensation/dimerization products. This work is the first to perform the structural and configurational assignments of bis-indane-1,5-diketones.